OS05.7.A Absence of severe hematological toxicity during first line treatment predicts low chance on severe toxicity during second line alkylating chemotherapy in glioblastoma. (9th September 2021) - van den Elzen, F E L; Grun, N; Osinga, J; van der Vegt, A N; de Glopper, L; Sintemaartensdijk, M; van Linde, M E; Postma, T J; Schuur, M; Kouwenhoven, M C M
Abstract: BACKGROUND: Glioblastoma has an infiltrative growth pattern that makes complete resection of the tumor virtually impossible. Sooner or later the tumor progresses, even after aggressive treatment with maximal safe resection, radiotherapy and/or chemotherapy. Hematological toxicity is an important cause of treatment delays during 1 st line treatment. How often hematological toxicity occurs during 2 nd line treatment is unclear. We explored rates of hematological toxicities in patients treated with temozolomide or lomustine at progression and investigated the association between severe toxicity during 1 st and 2 nd line treatment. METHODS: We studied a retrospective cohort study of adult patients (n=247) with a glioblastoma treated with 2 nd line alkylating chemotherapy at the Brain Tumor Center Amsterdam between 2000 and 2020. First line treatment of these patients consisted of a combination of radiotherapy combined with different treatments (80% received temozolomide, 4% PCV, 6% other chemotherapy and 10% radiotherapy only). Second line treatment consisted of temozolomide or lomustine. Mild and severe hematological toxicity were defined according to the CTCAE (version 5.0) criteria as a grade 1&2 and grade ≥3, respectively. We used descriptive statistics to analyze frequencies of hematological toxicity in patients with glioblastoma treated with 2 nd line chemotherapy. RESULTS: Sixty percent (147/247) of patients treated with 2 nd line chemotherapy experienced hematological toxicity (grade 1–4). Considering subtypes of hematological toxicities, more patients experienced hematological toxicity during 2 nd line treatment; severe thrombocytopenia occurred most frequently observed (6, 1 during 1 st line vs. 10, 5% during 2 nd line treatment), followed by neutropenia (3, 6 vs. 6, 9%), leukocytopenia (4, 0 vs. 5, 3%) and anemia (0 vs. 0, 8%). Fewer patients treated with 2 nd line temozolomide (n=113) experienced mild and severe hematological toxicity than patients treated with 2 nd line lomustine (n=134; 46% versus 71% (for mild) and 12% vs 21% (severe toxicity), respectively). A subset of 107 patients was initially treated with radiotherapy and concurrent and adjuvant temozolomide; within this subset, patients with none or only mild toxicity during 1 st line treatment had only a small risk of severe hematological toxicity during 2 nd line treatment (4%). In contrast, the 34, 5 % of patients with severe hematological toxicity during 1 st line treatment also experienced severe hematological toxicity during 2 nd line alkylating chemotherapy. CONCLUSION: Hematological toxicity occurs more frequently during 2 nd line treatment. Treatment with 2 nd line temozolomide results in less hematological toxicity than lomustine. Absence of severe toxicity during 1 st line treatment is predictive for the risk of toxicity during 2 nd line treatment.